(3TQM GdaJhMi Ydi eNJUQ JMQjQ Gdefbhds - (3CMeO GdaJhMis; (3CMeO GdaJhMjs ((3CHhGdLhGO GHQGgje Hf eadM s)
(3ChdgG (B:s
(3GHJOG GdeUfahf cJHge HGdHSedI JHQckG HgG s
(3BNQgG (B:s
(3Ke QcHJ HYVgG eY HYV MUd CehQ dGJcGO JfMUQ s
(3GdfSNI HgG MhGTs
(3JMQjQ Gdefbhd dYdGA GdOjf Ydi Hf SdjeGf GdeQOGhi GdMfHdi J SfI (B885 (3GfXQ cTa GdXfhf L (B1 (3U` (B357s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3CUhd Gdabgs